The effectiveness of a training program based on the use of cloud Computing in developing reflective teaching skills and improving the self-efficacy of Mathematics Teachers in The Kingdom of Saudi Arabia - Elseidy, Mansour Samir (Journal of Educational and Psychological Sciences, 2022)
The research aimed to identify the effectiveness of a proposed training program based on cloud computing applications in developing reflective practices and self-efficacy among mathematics teachers in the Kingdom of Saudi Arabia. As a teacher, they applied the experimental program and the study tools represented in the cognitive achievement test related to reflective teaching skills, the note card for the performance aspects of practicing reflective teaching skills, and the self-efficacy scale. The results of the research revealed the effectiveness of the program in what it aimed at. Where a statistically significant difference was found at the level (α ≤ 0.01) between the mean scores of the research sample who studied the program in the pre and post applications of the achievement test and the observation card for reflective teaching skills, and the self-efficacy scale in favor of the post application, and the research recommended the need to adopt reflective teaching, tools and strategies In preparing and developing programs for preparing mathematics teachers before and during the service, in addition to increasing the number of training hours in educational preparation, it is necessary to generalize the training program based on cloud computing applications, and study its effectiveness in developing the knowledge and skill aspects of teachers.